γ-Mangostin attenuates osteoclastogenesis and bone resorption by suppressing the PI3K/AKT/NF-κB pathway - Wei, Jian; Xie, Jiayue; He, Zhiyang; Feng, Xiaofeng (Frontiers in Pharmacology, 2026)
BackgroundPostmenopausal osteoporosis (PMOP), driven predominantly by estrogen deficiency-induced hyperactivation of osteoclasts, represents a critical public health burden. The pursuit of naturally sourced inhibitors of osteoclast function with minimized adverse effects remains a pivotal research endeavor. γ-Mangostin (γ-Mag), a natural xanthone derived from the pericarp of mangosteen, possesses broad anti-inflammatory and anti-tumor activities. Nevertheless, its influence on bone metabolic homeostasis, particularly osteoclast biology, remains entirely unexplored. This study aims to elucidate the impact of γ-Mag on osteoclast differentiation and function, and to evaluate its therapeutic potential for PMOP.MethodsPrimary rat bone marrow-derived macrophages (BMMs) were isolated and stimulated with RANKL to establish an in vitro osteoclastogenesis model. The effects of γ-Mag on osteoclast formation and function were assessed through TRAP staining, F-actin ring immunofluorescence, and bone slice resorption pit assays. Mechanistic insights were gained by examining the PI3K/Akt/NF-κB pathway and downstream osteoclastogenic factors (C-FOS, NFATc1) using qRT-PCR, Western blot, and immunofluorescence. The in vivo efficacy was validated in an ovariectomized (OVX) rat model of PMOP, with bone microarchitecture and remodeling parameters analyzed via Micro-CT and bone histomorphometry.ResultsAt non-cytotoxic concentrations (≤4 μM), γ-Mag potently and concentration-dependently suppressed RANKL-induced osteoclast formation, disrupted F-actin ring integrity, and impaired bone resorptive activity. Mechanistically, γ-Mag significantly attenuated the RANKL-triggered activation of the PI3K/AKT/NF-κB signaling axis, as demonstrated by reduced phosphorylation of PI3K, AKT, p65, and IκB. This upstream suppression consequently led to the downregulation of the pivotal transcription factors C-FOS and NFATc1, and inhibited NFATc1 nuclear translocation. In vivo, γ-Mag administration (10 mg/kg, i.p., every other day for 8 weeks) markedly ameliorated bone loss and restored compromised bone microarchitecture in OVX rats, which was associated with reduced osteoclast numbers and decreased expression of ACP5, CTSK, C-FOS, and NFATc1 in bone tissue.ConclusionOur findings demonstrate that γ-Mag inhibits osteoclastogenesis and bone resorption by targeting the PI3K/AKT/NF-κB pathway, thereby blunting the C-FOS/NFATc1 transcriptional program. This study establishes γ-Mag as a promising natural lead compound for the treatment of postmenopausal osteoporosis.